converting heat energy from urban dwellings into electricity - (:unkn) unknown (My University, 2023)
Housing construction in Africa, particularly in the Republic of Congo, requires no special regulations, and the generally impoverished populations build their homes with little regard for comfort and energy consumption. Most urban dwellings are very energy-intensive. As a result, thermal discomfort in the home is accentuated.Isn't it possible to make good use of the heat available in urban housing, by transforming it into electricity?This is the ambition we present in this paper.
Keywords: African Research